Efficacy of dexamethasone combined with intravenous immunoglobulin for the treatment of pediatric autoimmune encephalitis - Zhou, Xiaolin; Luo, Xiangyang; He, Zhanwen; Tang, Danxia; Li, Yu; Li, Pinggan (Frontiers in Neurology, 2025)
IntroductionGlucocorticoids and intravenous immunoglobulin (IVIG) have been established as the primary therapeutic agents for treating autoimmune encephalitis (AE). Methylprednisolone is the most frequently utilized glucocorticoid; however, the potential advantages of dexamethasone (DEX) in the management of encephalitis have yet to be fully elucidated. This study aimed to assess the efficacy of DEX in combination with IVIG in the treatment of pediatric AE.MethodsThis retrospective study included 41 pediatric patients who were diagnosed with AE and were categorized into two groups on the basis of their treatment history. Group A (n = 29) comprised children who initially received immunotherapy at other healthcare institutions but were referred to our hospital for DEX+IVIG treatment because of inadequate response to prior therapies. Group B (n = 12) consisted of children who were administered DEX+IVIG treatment early in the acute phase of AE at our hospital. The therapeutic outcomes of DEX+IVIG treatment in children with nonacute AE (Group A) and acute AE (Group B) were evaluated. The modified Rankin scale (mRS) was used to assess the clinical status of all participants.ResultsNinety percent of the patients were severely ill prior to DEX+IVIG treatment (mRS = 3.8 ± 1.0). Following treatment, the clinical symptoms of children in both the nonacute stage (Group A) and the acute stage (Group B) significantly improved. At the final follow-up, 90.2% of patients (mRS = 0–2) exhibited a favorable prognosis, with a complete response rate (mRS = 0) of 43.9% and a relapse rate of 2.4%. Children who experienced relapse were treated with DEX+IVIG, leading to a positive outcome. No severe adverse events were observed during treatment. The results of this study indicated that DEX+IVIG is an effective treatment for children with acute, nonacute, and relapsing AE.DiscussionDEX+IVIG was shown to be beneficial at the acute, nonacute, sequelae, and recurrence stages of AE.